2022
DOI: 10.3389/fpsyg.2021.797269
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nuanced Links Between Internet Use and Subjective Well-Being Among Older Adults: A Nordic Population-Based Study

Abstract: AimThe aim was to explore the various associations between subjective well-being and internet use among older adults in two regions in Finland and Sweden.MethodsThe data was collected through a population-based survey (N = 9,386) as part of the GERDA project conducted in 2016. The connection between subjective well-being (measured by perceived meaningfulness, happiness and life satisfaction) and internet use (distinguishing between internet users, non-users and users with support, and diverse internet activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…According to Zhou et al (2015), cultural indulgence strengthens the effect of hedonic value on affective commitment in social virtual worlds and also weakens the effect of utilitarian value. A population-based survey by Viklund and Forsman (2022) found statistically significant associations between, in particular, independent and informal internet use and all dimensions of subjective well-being (i.e. perceived meaningfulness, happiness and life satisfaction).…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…According to Zhou et al (2015), cultural indulgence strengthens the effect of hedonic value on affective commitment in social virtual worlds and also weakens the effect of utilitarian value. A population-based survey by Viklund and Forsman (2022) found statistically significant associations between, in particular, independent and informal internet use and all dimensions of subjective well-being (i.e. perceived meaningfulness, happiness and life satisfaction).…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…E.Viklund, A.K.Forsman studied the connection between subjective well-being (measured by perceived meaningfulness, happiness and life satisfaction) and internet use (distinguishing between internet users, non-users and users with support, and diverse internet activities). Statistically significant associations were found between perceived life meaningfulness and internet use [11].…”
Section: Figmentioning
confidence: 91%
“…Meetings, classes, daily gatherings, and the transmission of information related to infectious diseases, were carried out online, so the population most affected by digital technology was older adults, which undoubtedly posed a significant risk to their quality of life. According to previous studies, middle-aged and older adults who actively use the internet and other digital technologies are more likely to alleviate social isolation and lead active daily lives [50]. Specifically, Szabo et al [51] confirmed that middle-aged and older adults who actively engage in social activities via the internet felt decreased loneliness and increased well-being with increased participation in activities.…”
Section: The Relationship Between Ict Use and Perceived Life Satisfac...mentioning
confidence: 94%